Intersecting Colors Josef Albers and His Contemporaries - Malloy, Vanja (Amherst College Press, 2015)
Josef Albers (1888-1976) was an artist, teacher, and seminal thinker on the perception of color. A member of the Bauhaus who fled to the U.S. in 1933, his ideas about how the mind understands color influenced generations of students, inspired countless artists, and anticipated the findings of neuroscience in the latter half of the twentieth century. With contributions from the disciplines of art history, the intellectual and cultural significance of Gestalt psychology, and neuroscience, Intersecting Colors offers a timely reappraisal of the immense impact of Albers's thinking, writing, teaching, and art on generations of students. It shows the formative influence on his work of non-scientific approaches to color (notably the work of Johann Wolfgang von Goethe) and the emergence of Gestalt psychology in the first decades of the twentieth century. The work also shows how much of Albers's approach to color-dismissed in its day by a scientific approach to the study and taxonomy of color driven chiefly by industrial and commercial interests-ultimately anticipated what neuroscience now reveals about how we perceive this most fundamental element of our visual experience. Edited by Vanja Malloy, with contributions from Brenda Danilowitz, Sarah Lowengard, Karen Koehler, Jeffrey Saletnik, and Susan R. Barry.